Respuesta :
Answer:
(x+2)(x-6)=x^2 - 4x -12
(x-4)(x+3)=x^2 - x - 12
(x-12)(x+1)=x^2 - 11x - 12
(x-3)(x+4)=x^2 + x - 12
Step-by-step explanation:
You do the calculations:
(x + a) (x + b) = x^2 +ax + bx + ab = x^2 + (a+b) + ab, where a and b are real numbers. (At least in this case)
The factored form of the expression as shown are [tex]x^2 - x - 12, \ x^2 - 11x - 12, \ x^2 - 11x - 12 \ and \ x^2 + x - 12[/tex]
Expanding factored form of quadratic equation
Given the following functions;
[tex]f(x) = (x + 2)(x -6) = x^2 - 6x + 2x - 12\\f(x)= x^2 - 4x - 12[/tex]
For the function'
[tex]f(x) = (x - 4)(x+3) = x^2 + 3x - 4x - 12\\f(x) = x^2 - x - 12[/tex]
For the function f(x) = (x – 12)(x+1)
[tex]f(x) = x^2 + x - 12x - 12\\f(x) = x^2 - 11x - 12[/tex]
For the function f(x) = (x – 3)(x +4)
[tex]f(x) = (x -3)(x +4) =x^2 + 4x - 3x - 12\\f(x) = x^2 + x - 12[/tex]
Learn more on factoring here; https://brainly.com/question/25829061
#SPJ2